Isolated nocturnal hypertension in relation to host and environmental factors and clock genes. Issue 10 (9th August 2022) - Huang, Jian‐Feng; Zhang, Dong‐Yan; Sheng, Chang‐Sheng; An, De‐Wei; Li, Mingxuan; Cheng, Yi‐Bang; Guo, Qian‐Hui; Wang, Ying; Wang, Ji‐Guang; Li, Yan
Abstract: Isolated nocturnal hypertension (INH) is a special type of out‐of‐office hypertension. Its determinants and pathophysiology remain unclear. In a nested case‐control study, we intend to investigate the host, environmental, and genetic factors in relation to INH. Among 2030 outpatients screened from December 2008 till June 2015, 128 patients with INH were identified, and then 128 normotensives were matched according to sex and age. INH was an elevated nocturnal blood pressure (BP ≥120/70 mmHg) in the presence of a normal daytime BP (< 135/85 mmHg). Host factors included age, sex, body mass index, smoking and drinking, sleep time and duration, heart rate, serum lipids, and serum creatinine. Environmental cues encompassed season, ambient temperature, atmospheric pressure, humidity, and wind speed, and genetic cues 29 single‐nucleotide polymorphisms (SNPs) in 12 clock genes. Daytime and nighttime BPs averaged 124.9/80.7  and 114.5/73.7 mmHg, respectively, in the INH patients and 121.0/76.5 and 101.8/63.3 mmHg in the normotensive controls. Stepwise logistic regression analyses revealed that INH was associated with nighttime heart rate ( P  = .0018), sleep duration ( P  = .0499), and relative humidity ( P  = .0747). The odds ratios (95% CI) for each 10 beats/min faster nighttime heart rate and 10% lower relative humidity were 1.82 (1.25‐2.65) and 0.82 (0.67‐1.00), respectively. Irrespective of the genetic models, no significant association was observed between INH and the SNPs ( P ≥ .054). In conclusion, INH was associated with host and environmental factors rather than genetic markers.